Toward the design of Zn–Al and Zn–Cr LDH wrapped in activated carbon for the solar assisted de-coloration of organic dyes. Issue 86 (1st September 2016) - Khan, Shahid Ali; Khan, Sher Bahadar; Asiri, Abdullah M.
Abstract : Designing of materials for the extraction of organic toxins are the critical factors for environmental remediation. Abstract : Designing of materials for the extraction of organic toxins are the critical factors for environmental remediation. In the present study, a layered double hydroxide (LDH) of the binary compounds Zn–Al and Zn–Cr wrapped in activated carbon were synthesized through the co-precipitation method. These catalysts were characterized by FESEM, XRD, EDS, XPS, FTIR, PL and DRS. These catalyst were evaluated for the adsorption-assisted photodegradation of acridine orange (AO), malachite green (MG), crystal violet (CV), congo red (CR) and methyl orange (MO) dyes. The adsorption-assisted photodegradation was studied in four different parameters: dark, visible, ultraviolet and sunlight exposure conditions. Under various light effects, AO was selectively removed and Zn–Al/C-LDH showed stronger activity then Zn–Cr/C-LDH. Both catalysts showed approximately 90% removal efficiency of AO in sunlight. PL and DRS data showed prominent bands for the respective catalysts in the visible region. Zn–Al/C-LDH and Zn–Cr/C-LDH showed band gaps of 2.97 eV and 2.91 eV, respectively. Zn–Al/C-LDH showed very good recyclability and durability until the fourth cycle and still remained active after the fourth cycle as compared to Zn–Cr/C-LDH, which also showed good recyclability until the fourth cycle, but remained inactive after the fourth cycle. It was also observed that the specific light intensity and the substrate-catalyst specificity required equal consideration during the development of these new catalysts.